Diagnostic Role of Lung Ultrasound in Pneumonia - Putu Gita Indraswari; I Desak Putu Agung Krisdanti; Faradilla Novita Anggreini (Indonesian Journal of Global Health Research, 2026)
Pneumonia remains a leading cause of morbidity and mortality worldwide, particularly among hospitalized and critically ill patients. Diagnosis is traditionally based on clinical evaluation and chest radiography; however, overlapping clinical features with other respiratory diseases and limited access to radiographic imaging may result in diagnostic delays or inaccuracies. Lung ultrasonography has increasingly been recognized as a useful bedside imaging modality due to its portability, lack of ionizing radiation, and favorable diagnostic performance. This review aims to describe the underlying mechanism of lung ultrasonography, outline characteristic ultrasonographic findings in pneumonia, and evaluate its diagnostic value, including advantages and limitations, in clinical practice. A narrative literature review was conducted using electronic databases including PubMed, Scopus, Google Scholar, and ScienceDirect. Peer-reviewed articles, meta-analyses, clinical studies, guidelines, and authoritative textbooks related to lung ultrasound and adult pneumonia were included than published since 2021-2024. Data were analyzed descriptively, focusing on ultrasonographic features and diagnostic accuracy parameters. Lung ultrasound reveals a spectrum of findings corresponding to disease severity, including focal B-lines and pleural irregularities in early pneumonia, followed by lung consolidation characterized by shred sign, air bronchograms, and tissue-like (hepatization) appearance in advanced stages. Evidence from meta-analyses consistently demonstrates high diagnostic accuracy, with sensitivity and specificity generally exceeding 85–90%, often surpassing chest radiography. Lung ultrasonography is a reliable and practical imaging modality for the diagnosis of pneumonia. Given its high diagnostic accuracy and clinical advantages, lung ultrasound should be considered an important adjunct or alternative to conventional imaging, particularly in emergency, intensive care, and resource-limited settings.